A Midwest district: impact of preferred name policies and procedures on LGBTQIA2S+ educators - Torres-Wigton, Lisa Carmín (My University, 2025)
During 2020-2021 the Midwest District joined many school districts across the United States (Eckes, S., 2020; Elassar, A., 2022; Kopels, S., 2023) in determining how to serve the needs of their transgender and nonbinary students with the use of preferred names and/or pronouns. The policies and procedures delivered to the Midwest District’s staff members provided revealed some personal opinions regarding people within the LGBTQIA2S+ community [(L)esbian, (G)ay, (B)isexual, (T)ransgender, (Q)ueer/(Q)uestioning, (I)ntersexual, (A)sexual/(A)romantic/(A)gender, (2)Two-Spirited, (+) other genders/identities undefined] and the lack of protection provided by the Midwest District to those staff members. Despite some well-intentioned questioning regarding gender expression and identity, what was unintentionally revealed was a consistent bias towards the LGBTQIA2S+ community as a whole. This case study seeks to inform the existing body of research on how teachers within the LGBTQIA2S+ community working in the Midwest District perceive not only the effect of their policies and procedures, but whether they align of the Midwest District’s values. This research is a qualitative case study of six interviews that focused on five questions. The participants were employed at the Midwest District between 2020-2021 school year and identify LGBTQIA2S+. There were six participants: three teachers (1 elementary, 1 middle, 1 high school) and three administrators (2 primary and 1 secondary). After the interviews, analytic memo-ing, open coding, and magnitude coding revealed three concepts that are alike in both groups of participants: (sense of respect, training, policies) and that while both teachers and administrators feel supported and respected, there are elements within the Midwest District’s that are discriminatory.
Keywords: District; LGBTQIA2S+; Policies; Procedures; Preferred names and pronouns